Western Corporate Credibility: Is it applicable in Malaysia? - Soetrisno, Fathan; Dyg Affizzah, A.M.; Irma Yazreen, Yusuf (Human Resource Management Academic Research Society, 2020)
Credibility is an essential element for corporate to hold individual trust and confidence towards the corporate. Despite many elements that may influence the credibility of a corporate, less researches concentrate on factors that may affect corporate credibility as a whole in different dethronement particularly in Malaysian perspective. Thus, the study focuses on element derived from Western corporate credibility index and adding factors that may affect corporate credibility from Malaysian perspectives. The finding of the study indicates that factors that affect corporate credibility from Malaysian perspectives are Honesty, Customer Focus, Celebrity Engagement and Innovation. The results of the study can be an important inspiration to implement suitable strategies to enhance corporate credibility particularly in Malaysia.